Pengaruh Perceived Value dan Tourist Experience terhadap Tourist Loyalty dengan Tourist Satisfaction sebagai Variabel Mediasi (Studi Kasus pada Wisata Lawang Sewu Semarang) - Muhammad Asyiq Ardana; Bahrain Pasha Irawan (ARZUSIN, 2026)
Fluctuations in the number of tourist visits to Lawang Sewu Semarang indicate the importance of strategic efforts to increase tourist loyalty. Tourist loyalty is influenced by various factors, including perceived value and tourist experience, with tourist satisfaction as a mediating variable. This study aimed to analyze the influence of perceived value and tourist experience on tourist loyalty through tourist satisfaction. This study used a quantitative approach with an explanatory design. Data were collected through questionnaires administered to 120 respondents who were visitors to Lawang Sewu, using purposive sampling. The data were analyzed using SmartPLS. The results showed that perceived value and tourist experience had positive and significant effects on tourist satisfaction. In addition, tourist satisfaction had a positive effect on tourist loyalty. Perceived value and tourist experience also had direct effects on tourist loyalty, as well as indirect effects through tourist satisfaction as a mediating variable. Thus, increasing perceived value and positive tourist experiences can enhance satisfaction and encourage the formation of tourist loyalty toward Lawang Sewu Semarang.